Multi-Functional Filtering Power Divider with a Reconfigurable Frequency and Ultrawide Isolator Functionality - Girdhari Chaudhary; Daewoo Choi; Yongchae Jeong (Journal of Electromagnetic Engineering and Science)
In this paper, we describe the co-design of a multi-functional non-reciprocal filtering power divider (NR-FPD) with ultrawide reverse isolation and frequency reconfigurable functionality. The proposed NR-FPD offers an arbitrary power division ratio (PDR) with low transmission loss in the forward direction and non-reciprocal behavior along with an ultrawide high reverse isolation bandwidth in the backward direction. For a better understanding of the behavior of the proposed NR-FPD, analytical equations of spectral S-parameters were derived. These equations allowed for the selection of optimum circuit and modulation parameters without the need for harmonic balance simulation. The ultrawide high reverse isolation bandwidth was achieved through the proper selection of optimum modulation parameters. For the proof of concept, the NR-FPD with an equal PDR was fabricated and characterized. Measurement results showed that the frequency was continuously tuned between 1.62 GHz to 1.95 GHz, and there was insertion loss of 5.70 dB in the forward direction of transmission and an ultrawide 20 dB isolation bandwidth in the backward direction of transmission.